EFL students’ difficulties in writing a research proposal - Ninik Suryatiningsih (International Journal of Humanities and Innovation (IJHI), 2019)
This study aims to investigate EFL students’ difficulties in writing a research proposal by using Swales’ Create-A-Research-Space (cars) model and try to find out the students’ problems. This study was used as a qualitative research design. The subject of this study are twenty students and the instrument are students writing the research proposal, interview for the students and lecturer. The result of this research is the students’ problem in writing for their introduction for move 1 (75%) and for move 2 (55%), there are 4 (four) students having problems how to face the criteria for inclusion and exclusion from review was not justified and the literature review was not topic focused. Related to methodology, the choice of paradigm, methodology, data collection, and data analysis was not justified to answer the research questions (20%). Next, a detailed description of the research procedures, as well as an explanation of the reason for doing so, was not provided (15%). Continued to the detailed description of procedures and materials was not provided to allow for replication (15%). Moreover, a component of methodologies such as the research design, research site, and participants, data collection techniques, and data analysis is not included (15%). The last, for the references, were all student writing research proposals less to completed the way how to write a reference, such as uncompleted detailed related to sources. The biggest problem related to the students' ability to write a research proposal for the introduction. Some students face some difficulties in how to compose the background well, including introducing and reviewing items of previous research in the area, how to find a gap in the previous research and student's fewer references to quote.